Notes on a tree: reframing the relevance of primate choruses, duets, and solo songs. Issue 3 (4th May 2022) - De Gregorio, Chiara; Carugati, Filippo; Valente, Daria; Raimondi, Teresa; Torti, Valeria; Miaretsoa, Longondraza; Gamba, Marco; Giacoma, Cristina
Abstract : The complexity of primates' singing behavior has long gathered the attention of researchers interested in understanding the selective pressures underpinning the evolution of language. Among these pressures, a link between territoriality, pair-living, and singing displays has been suggested. Historically, singing primates have been found in a few taxa that are not closely related to each other, and, in the last years, their phylogeny has dramatically changed. Hence, we aimed at understanding if the dogmatic association between territorial behavior and a monogamous social structure still holds in the light of current research. Moreover, singing behavior has often been considered a whole, but animals can perform different singing forms depending on how many individuals call simultaneously. Currently, it is unclear to which extent these singing forms are widespread among these primate groups. Given that there is no unique definition for a "song", "solo", "duet", and "chorus", we envisioned some of the most used descriptions. We then formulated some new definitions that we followed in our review of the presence/absence of these different forms of song organization among singing primates' taxa. In particular, we suggested that tarsier species that are typically considered non-singers may indeed sing, and we pointed out that non-duetting gibbons may perform duet interactions. We found that, besides duets, chorusing behavior and solo songs are essential features of primates' communication, but their study is still in a descriptive phase. Moreover, while territorial behavior seems to be conserved in these singing taxa, we highlighted that the monogamous social structure is not the rule. Pair-living plus multi-females groups displaying singing behavior are common too. We suggest that ending to consider these taxa as uniform in their sociality and vocal behavior might be a significant turning point to unravel the different selective pressures that influenced the emergence and organization of such peculiar vocal behavior.